2020
DOI: 10.1093/botlinnean/boz088
|View full text |Cite
|
Sign up to set email alerts
|

Towards a phylogenetic classification of the Ocotea complex (Lauraceae): an analysis with emphasis on the Old World taxa and description of the new genus Kuloa

Abstract: Ocotea is one of the largest genera in the Lauraceae (c. 400 spp.), and it has been known to be paraphyletic with respect to most other genera of the New World Lauraceae for almost 20 years. In the traditional circumscription, Ocotea contains not only Neotropical species, but also about 45 species from the African region, including Macaronesia, Madagascar, and the Comoro and Mascarene Islands. Only a few of the species have been included in previous molecular systematic analyses. Here we present a phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 30 publications
2
38
1
Order By: Relevance
“…Within genera, characters such as hollow branches, angled branches, petiole thickness, venation, domatia, flower size, position of tepals, filament thickness in relation to the anther, presence of staminodes, fruit length/diameter ratio, and cupule depth and margins, are valuable in differentiating species. Recent anatomical studies have found that leaf cuticular characters (e.g., thickness around the stomata) may be of taxonomic value (Nishida and van der Werff, 2011; Nishida et al, 2016; Trofimov and Rohwer, 2020), but this information is available currently for only a few species, preventing its taxonomic use in the Ocotea complex.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Within genera, characters such as hollow branches, angled branches, petiole thickness, venation, domatia, flower size, position of tepals, filament thickness in relation to the anther, presence of staminodes, fruit length/diameter ratio, and cupule depth and margins, are valuable in differentiating species. Recent anatomical studies have found that leaf cuticular characters (e.g., thickness around the stomata) may be of taxonomic value (Nishida and van der Werff, 2011; Nishida et al, 2016; Trofimov and Rohwer, 2020), but this information is available currently for only a few species, preventing its taxonomic use in the Ocotea complex.…”
Section: Figurementioning
confidence: 99%
“…The lack of taxonomically useful data is matched by the paucity of genetic information. The few molecular studies of this complex (Chanderbali et al, 2001; Trofimov et al, 2019; Trofimov and Rohwer, 2020) have used a small number of molecular markers, providing only limited resolution of the relationships among species, and failing to confidently resolve deeper relationships. Thus, we still have a poor understanding of relationships within the Ocotea complex, which impedes progress in our understanding of the evolution of this early‐diverging and ecologically important lineage.…”
Section: Figurementioning
confidence: 99%
“…Ocotea is the largest genus of Lauraceae in the Neotropics, with distribution from Mexico to Argentina. Estimated numbers of species belonging to the genus have been raised to 400 Neotropical species (van der Werff, 2011), and about 45 species from the Africa region, including Macaronesia, Madagascar, and the Comoro and Mascarene Islands (van der Werff, 1996, 2013; Trofimov and Rohwer, 2020). Moreover, in more recent years, other 90 species were published and one transferred to the genus (see Moraes, 2018; Moraes and Vergne, 2019; van der Werff, 2018a,b; Moraes et al, 2019; van der Werff, 2020), which make Ocotea to have about 450 (van der Werff, 2020) to 500 species currently accepted.…”
Section: Introductionmentioning
confidence: 99%
“…Several phylogenetic studies (Chanderbali et al, 2001; Trofimov et al, 2016, 2019; Rohde et al, 2017; Trofimov and Rohwer, 2020) have shown that Ocotea is polyphyletic, or paraphyletic with respect to all other genera of the named “ Ocotea complex” (in sense of Chanderbali et al, 2001), which includes Aniba Aubl., Endlicheria Nees, Licaria Aubl., Nectandra Rottb., and Pleurothyrium Nees, for instance. Trofimov et al (2019) have reinstated the genus Mespilodaphne Nees & Mart.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation